Bridging Mind and Market: A Bibliometric Exploration of Consumer Motivation's Role in Shaping Behavioral Intentions - Hi Yusuf, Ibnu Sina; Wiyaja, Febiyola; Husen, Irmawati A (Fakultas Ekonomi Universitas Kadiri, 2025)
The digital era and globalization have created increasingly complex market landscapes where understanding consumer motivation becomes crucial for organizations seeking competitive advantage. This research aims to comprehensively map and analyze the intellectual structure of the research domain exploring consumer motivation's role in shaping behavioral intentions through systematic bibliometric analysis. The study employs a quantitative bibliometric approach utilizing advanced scientometric techniques to examine large-scale bibliographic data, with secondary data comprising 250 scientific articles extracted from Scopus and Google Scholar databases covering publications from 2018 onwards. The PRISMA framework was implemented for structured article selection, while VOSviewer software facilitated comprehensive bibliometric analysis through co-authorship networks, keyword co-occurrence mapping, citation analysis, and thematic clustering. Network analysis reveals that intrinsic and extrinsic motivation remain central nodes dominating the research landscape, with Self-Determination Theory maintaining its position as the dominant theoretical framework. The findings demonstrate significant interdisciplinary integration, with concepts from cognitive psychology, social psychology, and organizational psychology converging within unified theoretical frameworks. Temporal analysis indicates research evolution from traditional utility-focused approaches toward more holistic perspectives integrating hedonic, social, and symbolic motivations. The study identifies emerging themes including sustainable consumption, collaborative consumption, and prosocial motivation, reflecting contemporary societal concerns and digital transformation impacts on consumer behavior, ultimately contributing to advancing theoretical understanding by providing comprehensive overview of knowledge structure evolution and identifying convergence points across disciplines.